ANTI FUNGAL ACTIVITY OF METHANOLIC EXTRACT OF Usnea sp. AGAINST Malassezia furfur - Rukayadi. Y -; Diantini. A -; Lestari K. - (Bionatura, 2012)
The antifungal activity of methanolic extract of Usnea sp. (MEU) against Malassezia furfur ATCC 14521, in terms of in vitro susceptibility, minimum inhibitory concentration (MIC) and minimum fungicidal concentrations (MFC) were investigated using broth microdilution method with endpointafter 48 h. Time-kill curves were determined at concentrations 0~, 1/2~, 1~, 2~, 4~ and 8~MIC. MEU was susceptible against M. furfur with diameter clear zone of 34 mm for 1 mg/ml. MIC and MFC values were 16 ƒÊg/ml and 64 ƒÊg/ml, respectively. Time-kill curve demonstrated that treatment with 4~MIC (64 ƒÊg/ml) and 8~MIC (128 ƒÊg/ml) of MEU for 4 h and 1 h, respectively, was able to kill 100 % of M. furfur. MEU shows potential as an antifungal agent for inhibiting the growth of M. furfur ATCC 14521 in vitro. MEU might be a useful alternative for treating dandruff, tinea versicolor, tinea capitis, and seborrhoeicdermatitis due to the growth inhibition of M. furfur.Key words: antifungal, in vitro Malassezia furfur, methanolic extract of Usnea sp. (MEU)